Modulated conductive bridge memory characteristics by radio frequency input and non‐volatile switching of frequency multiplication. Issue 21 (30th August 2022) - Yin, Yifei; Uchida, Chihiro; Tsukamoto, Keito; Hayashi, Hitoshi; Nakaoka, Toshihiro
Abstract: The authors present an Ag‐GeTe‐based conductive bridge memory that allows radio frequency (RF) input and transmission. The RF input modifies the resistance switching characteristics and the memory device can switch the order of harmonics of the transmitted RF wave. The transmittance for the RF input above 500 MHz was higher than 0.5 for both the low‐resistance state (LRS) and the high‐resistance state (HRS). Below 500 MHz the transmittance decreased with decreasing frequency and depended on the resistance state (LRS or HRS). At 20 MHz, the transmission for the HRS was 0.02, while that for the LRS was 0.2. An RF input of 20 MHz at 10 dBm modified the SET voltage from 0.19 to 0.05 V, and the RESET voltage from −0.17 to −0.05 V. The RF wave transmitted through the LRS consisted almost entirely of fundamental waves, while that in the HRS provided harmonics or frequency multiplication up to the fifth order at 150 MHz at 10 dBm. Heat cycle measurements with RF input revealed the difference between the non‐linear resistance producing the frequency multiplication and the DC resistance.